2020
DOI: 10.1188/20.cjon.51-57
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Stress: Patient and Caregiver Experiences With Stressors During Hospitalization

Abstract: CANCER TREATMENT OFTEN CAUSES HIGH LEVELS OF STRESS, affecting patients' quality of life and outcomes and necessitating a holistic approach to care. Patients with cancer may also experience physiologic stress from the disease process or cancer treatment and its side effects. According to Hoffman, McCarthy, Recklitis, and Ng (2009), cancer survivors often report an increased prevalence of serious psychological distress, including patients who have been in remission for five years or longer. In addition, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…The emotional impact of breast cancer manifests in the form of anxiety, fear, and depression, which may persist for years after the end of treatment (Borgi et al., 2020 ; De la Torre‐Luque et al., 2020 ; Li et al., 2021 ). High levels of stress are also common among these patients (Abuatiq et al., 2020 ; Dooley et al., 2017 ; Harris et al., 2017 ; Li et al., 2021 ), and consequently, various studies have examined the impact this has on mental health (Abdollahi et al., 2019 ; Arnaboldi et al., 2017 ; Voigt et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The emotional impact of breast cancer manifests in the form of anxiety, fear, and depression, which may persist for years after the end of treatment (Borgi et al., 2020 ; De la Torre‐Luque et al., 2020 ; Li et al., 2021 ). High levels of stress are also common among these patients (Abuatiq et al., 2020 ; Dooley et al., 2017 ; Harris et al., 2017 ; Li et al., 2021 ), and consequently, various studies have examined the impact this has on mental health (Abdollahi et al., 2019 ; Arnaboldi et al., 2017 ; Voigt et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It shows a high internal consistency (α = 0.93) and evidence of internal structure [43]. Anxiety symptoms according to their scores are classi ed as normal (0-9), low anxiety (10-18), moderate anxiety (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and severe anxiety (30-63) [44].…”
Section: Anxious Symptomsmentioning
confidence: 99%
“…As for the psychological factor, ample evidence showed that knowing about the diagnosis of cancer is associated with an increase in depressive symptoms, anxiety, and stress [20][21][22][23]. Moreover, hospitalized patients have a higher prevalence of symptoms of depression, anxiety, and stress of these health problems, compared to outpatients [16,24]. Other factors related to increased symptoms of depression, anxiety, and stress in cancer patients include the high costs and economic expenses related to the treatment of the disease [20,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that β-AR signaling promotes tumor growth in part through enhancing MDSC accumulation and their immunosuppressive function ( Mohammadpour et al, 2019 ). This finding is especially disconcerting, given that patients with cancer frequently experience considerably higher levels of chronic stress following their diagnosis and during treatment ( Abuatiq et al, 2020 ). Since both β-AR signaling and FAO enhance MDSC suppressive function, we sought to determine whether β2-AR signaling alters the metabolic state of MDSCs and whether their immunosuppressive function is regulated through a novel β2-AR-FAO axis.…”
Section: Introductionmentioning
confidence: 99%